The Work Environment Ethics and its Role in Enhancing The Aspects of Job Creativity among Workers in Organizations Applied Study on the Employees of The General Authority for Al Amiria Presses - ARE - Ahmed, Hossam (The Arab Journal of Administration, 2020)
This study aimed to identify the relationship between workplace ethics and aspects of job creativity among employees of the General Authority for Amiri Press in Egypt, and to know whether there are statistically significant differences at the level of significance (a ≤ 0.05) in aspects of job creativity in the Authority’s employees due to the availability of the dimensions of an ethical work environment in the Authority or not. The population of the study was determined by the managers and employees at different job levels, and a questionnaire consisting of 40 questions was designed, with the correct response being 179 questionnaires (approximately 85 %). The study revealed that there is a positive relationship with statistical significance at the level of the significance of a ≤ 0.05 between the dimensions of work environment ethics combined and individual and the aspects of job creativity of the Authority’s employees.